Care Of Some Species Of The Magnoliaceae Family (Texas Journal of Agriculture and Biological Sciences, 2024)
This article provides some information on planting and maintaining some species of magnolia species, which are ornamental trees and shrubs, belonging to the magnolia family, and ensuring continuity of growth and development. the technology of the correct application of agrotechnical measures in the effective cultivation of the large-flowered magnolia plant was highlighted. At the same time, scientific work was carried out to determine the effect of seed selection and stratification on seed fertility and to compare the fertility of large-flowered magnolia plants growing in different climatic conditions in laboratory and field conditions, and the research results were explained.